MULTILITERACY APPROACH TO EDUCATIONAL CURRICULA AND THE APPLICABILITY OF COMICS AS POLYCODED TEXTS IN THE DEVELOPMENT OF DIFFERENT LEVELS OF FUNCTIONAL LITERACY - Ivanovska, Gabriela (Philological Studies, 2022)
An intensely digitalized world and the new forms of text-mediated communication, which increasingly include texts in which information is transmitted through various coding systems/modes (verbal, visual, auditory, tactile, etc.), suggest that literacy should be considered as a plural phenomenon (i.e. multiliterary and multimodal), and text as a polycoded and multimodal product. In this paper we are not interested in considering all the different approaches to defining texts, rather we will approach the text primarily from a semiotic-cultural aspect, i.e. culture as text and text as a heterogeneous complex multimodal phenomenon that "embodies" reality with the help of different sign systems. The focus of our interest will be on multiliteracy approaches in the creation and reading of texts, as well as new pedagogical practices and educational curricula that would develop functional literacy, and the recognition of different semiotic systems, and would also encourage individual critical thinking from an early age. To this end, we first look at the different terminology used when talking about multiliteracy and point out the similarities, differences, and the need for a distinction between multiliteracy, multimodality, and polycodedness in the processes of reception of texts and of their interpretation. In conclusion, we devote our attention to comics as polycoded texts, which, we believe, are undeservedly underestimated in the context of educational curricula and literary criticism, as well as analyze comics as excellent means for the adoption of multiliteracy and the development of different levels of functional literacy in young people.